Aligned polycaprolactone/polyaniline electrospun nanofibers for directing neural stem cell differentiation and neuron arrangement - Licciardello, Michela; Traldi, Cecilia; Bortolameazzi, Matteo; Testore, Daniele; Ciardelli, Gianluca; Tonda-Turo, Chiara (Frontiers in Biomaterials Science, 2024)
The use of engineered biomimetic substrates combined with neural stem cells (NSCs) constitutes a promising approach to develop reliable in vitro models of the nervous tissue. The fabrication of scaffolds with suitable compositional, topographical, and electrical properties is crucial for directing neural cell adhesion, differentiation, and arrangement. Herein, we propose the development of electroconductive polycaprolactone/polyaniline (PCL/PANI) electrospun mats as functional substrates for NSC culture. A rotating drum collector was employed to obtain fibers with aligned geometry. According to the results, the increase in alignment contributed to the reduction of fiber diameter and the increase of scaffold mechanical properties in terms of elastic modulus and tensile strength. In vitro experiments demonstrated the ability of PCL/PANI membranes to support NSC attachment and growth, as well as significantly foster neuronal differentiation. Furthermore, the presence of an aligned pattern was shown to effectively influence the arrangement of NSC-derived neurons, confirming the potential of this substrate for the design of a physiologically relevant culture platform for in vitro investigation of the nervous tissue.